Penggunaan Media Tiga Dimensi untuk Meningkatkan Hasil Pembelajaran IPA Daur Hidup Tumbuhan pada Anak Tunarungu Kelas VII SLB Muara Bulian - Santika, Yeni; Rahmahtrisilvia, Rahmahtrisilvia (Jurnal Penelitian Pendidikan Khusus, 2022)
This research is motivated by the problems found in the field where in the science learning process the plant life cycle material for children looks passive and children's grades have not reached the KKM. This makes children still need teacher guidance in the learning process. Researchers are interested in helping to overcome these problems through the use of three-dimensional media. The research method used is classroom action research which consists of two cycles. Each cycle consists of four face-to-face meetings and at the end of each learning cycle the evaluation is in the form of giving test questions. The cycle is carried out in several stages, namely planning, action, observation and reflection. Data collection techniques used are observation, interviews and tests. The results of this study indicate that children's learning outcomes in science subjects on plant life cycle materials have increased. This is obtained through research data that has been analyzed. Based on the results of this study, it can be said that the value of plant life cycle learning outcomes in deaf children can be increased through the use of three-dimensional media.